Efecto inhibitorio in vitro del extracto alcohólico de rosmarinus officinalis y argemone mexicana sobre el crecimiento de escherichia coli productora de betalactamasas de espectro extendido - Ruiz Barrueto, Miguel Angel (2016)
It is determined, the inhibitory effect in vitro of the alcoholic extract of leaves of Rosmarinus officinalis and Argemone mexicana on the growth of Escherichia coli producing extended-spectrum beta-lactamase, were evaluated ten different concentrations (10; 20; 30; 40; 50; 60; 70; 80; 90; 100 mg / mL) of ethanol extract of leaves of R. officinalis and A. mexicana. To evaluate the effect of ethanol extract of the bacterium two methods the plate diffusion discs and microplate microdilution method were used. In the first method 4 disks 6mm diameter containing 25uL of each extract concentration previously prepared and incubated at 37C for 24 hours they were placed, 8 duplicates were performed for each trial and experimentation 4 repetitions. The results were expressed as diameter (mm) of growth inhibition halo of ESBL-producing E. coli. In the microdilution method were placed in 10 wells 50 ul of 10 concentrations of the extracts at double concentration and the microplate was incubated at 37 ° C for 24. For the first method positive control (disks amoxicillin / antibiotics clavulanic considered and cefotaxime / clavulanate) and negative (absolute ethanol) and for the second method only negative control (distilled water and absolute ethanol). It was found that growth ESBL-producing E. coli is dependent on the concentration of ethanolic extract of leaves of R. officinalis and A. mexicana. Statistical analysis indicates that there is no significant difference between the averages of the halos of inhibition treatments evaluated for both extracts. It was determined that the minimum inhibitory concentration was <10 mg / m. We conclude that there Escherichia coli bacterial inhibition of ESBL to different concentrations of the alcoholic extracts of R. officinalis and A. mexicana. There is no statistically significant difference between the diameters of halos of inhibition treatments evaluated, with 95% reliability.